Edible Insects in Latin America: A Sustainable Alternative for Our Food Security - Abril, Silvana; Pinzón, Mariana; Hernández-Carrión, María; Sánchez-Camargo, Andrea del Pilar (Frontiers in Nutrition, 2022)
Nowadays, the food industry faces paramount challenges in different areas, since worldwide consumers are increasing every day, and at the same time, they are demanding new convenient products. Recent studies show that the current food production system is unsustainable over time and therefore is necessary to create new alternatives of production. New food trends are focused on the consumption of natural products, that have an eco-friendly production approach, and a beneficial nutritional profile for the consumer’s health. Hence, products are being created to not only have good organoleptic characteristics, but also to contain a wide variety of micro and macronutrients, and to be sustainable within their production. For this reason, the use of raw materials that satisfy the needs previously mentioned is being implemented. For instance, the use of insects as raw material, because they have a high protein content comparable to animal-based foods. Specifically, ants and crickets can contain between 9-77% protein of dry weight, while beef contains between 25-28%. On the other hand, insects present an ease and sustainable production system, compared to livestock farming, since some of them feed with food waste generated by humans. In addition, require less food for their upbringing; insects can convert 2 kg of feed into 1 kg of insect mass, while cattle use 8 kg of feed to produce 1 kg of body weight. On the other hand, there is evidence that insects produce fewer greenhouse gases during their production, for example, pigs produce between 10 and 100 times more greenhouse gases per kg of weight. United States, Mexico, Chile, Peru, and Argentina have begun to develop and consume these products; thus, promoting different and new ventures. Large-scale production of insect-based food products could help solve or even prevent the looming food problem and contribute to the sustainable development goals set by the United Nations. Thus, the aim of this review work was to compile and investigate the edible insect’s alternatives in Latin America, as well as the commercially available or potential derivative products. We discussed the nutritional value of edible insects, and how they could contribute to food security.